Interactions Among Host–Parasite MicroRNAs During Nosema ceranae Proliferation in Apis mellifera - Evans, Jay D.; Huang, Qiang (Frontiers in Microbiology, 2018)
We previously identified microRNA from N. ceranae and found that knockdowns of transcripts for the parasite protein Dicer greatly reduce parasite reproduction. In order to study parasitic miRNA functions and identify candidate target genes, we fed honey bees infected with Nosema ceranae with siRNA targeting the N. ceranae gene Dicer. We then deep-sequenced honey bee and N. ceranae miRNAs daily across a full 6-day proliferation cycle. We found seven honey bee and five N. ceranae miRNAs that were significantly differently expressed between the infection and siRNA-Dicer groups. N. ceranae miRNA showed potentially strong impacts on the N. ceranae transcriptome, where over 79% of the total protein coding genes were significantly correlated with one or more miRNAs. N. ceranae miRNAs also can regulate honey bee metabolism and immune response, given parasitic miRNAs were secreted into the cytoplasm. Our results suggest that N. ceranae miRNAs regulate both parasite and host gene expression, providing new insights for microsporidia parasitism evolution.